DIABETICO-PROTECTIVE ROLE OF VITAMIN D - Asif Memon; Saeeda Baig; Hamza Ahmed Farooqi; Fatima Zohra Habib (ziauddin University, 2019)
Studies worldwide have observed a link between VDR polymorphism and Diabetes Mellitus. Diabetes is a complex disease characterized by insulin deficiency caused by the alterations in the function of pancreatic β-cells, insulin sensitivity and systemic inflammation. Vitamin D deficiency has been identified as a contributing factor to Diabetes. Vitamin D acting via the nuclear vitamin D receptor (VDR) gene, located on human chromosome 12q12-q14, also acts as a transcription factor and regulates the beta cell secretion of Insulin. Studies have shown that vitamin D deficiency is widespread in those with diabetes but only few have studied the link between the two. Better understanding of the exact biochemical significance of vitamin d receptor polymorphisms and its association with metabolic disorders such as diabetes mellitus is required. To find out the association at the genetic level to combat the rampant prevalence of diabetes linked with VDR polymorphisms research engines employed were PubMed, Medline, etc. and articles selected were up to 2018. The objective of this review is to provide an overview regarding the Diabetico-protective role of vitamin D and its receptors and to discuss the polymorphism of VDR and the possible mechanism involved in the development of the disease.